Fitoquímica, Atividades Antimicrobiana e Antioxidante do Extrato Etanólico e Frações das Folhas de Jacaratia spinosa (Aubl.) A. DC. (Caricaceae) - Oliveira, Joelma Coelho Pina de (2015)
Jacaratia spinosa (Aubl.) A. DC. is a species of the Caricaceae family, popularly known as “jaracatiá” and “mamão-do-mato”. Widely distributed throughout the country, from the south of Bahia to Rio Grande do Sul. It occurs in rainforest and Cerrado, in gallery forest. It is a big tree to bloom in September and fruiting in January. In folk medicine Jacaratia spinosa is used as antimicrobial, anthelmintic, being displayed against hookworm. It is still used in wound healing and skin ulcerations. Studies in the literature suggest the presence of tannins and phenolic compounds in this plant with possible antimicrobial activity. The objectives of this study were dose the content of phenolic substances, perform the phytochemical from the leaves of Jacaratia spinosa and evaluate the antimicrobial and antioxidant activities of ethanol extract and fractions of leaves Jacaratia spinosa. The polyphenols, tannins and flavonoids content were determined in ethanol extract, acetone extract and its fractions. The antimicrobial activity was conducted on the same samples according to the recommendations of the Clinical and Laboratory Standards Institute (CLSI) to microdilution tests on broth, which allowed to determine the Minimum Inhibitory Concentration (MIC) against strains of Gram positive and Gram negative bacteria. In tests broth dilution also were applied to the determination of the antifungal sensitivity. For the antioxidant activity were used the DPPH methods, Co-oxidation of β-carotene / linoleic acid, FRAP, ABTS and differential pulse voltammetry to verify the antioxidant activity in the ethanol extract and the hexane, dichloromethane, ethyl acetate fractions, and the tannin aqueous fraction concentrated of the J. spinosa leaves. The results indicate that the highest amount of phenolic compounds in the leachate ethanol extract, wherein the total phenol content was found to be 13.86% and 12.72% total tannins (expressed in g tannic acid / 100 g material). In the antimicrobial tests, the tannins aqueous fraction concentrated (FAqCT) showed good activity to Gram-positive, bacteria Micrococcus luteus ATCC 9341 (MIC = 62.5 mg / mL) and Micrococcus luteus ATCC 10240 (MIC = 62.5 mg / mL ). The best result of antifungal activity was to Candida tropicalis ATCC 28707 in tannins aqueous fraction concentrated (MIC = 7.81 mg / mL) and aqueous fraction (MIC = 15.62 mg / mL). The antioxidant activity was tested by five methods, and for the DPPH method, the best result was found in the aqueous fraction (3.29 ol), the FRAP the most significant result was the ethanol extract (19.49 micromols Fe 2+ / mg) . In ABTS and β-carotene / Linoleic Acid methods the best results were to butanol fraction, 4.33 micromol Trolox / g for the ABTS method, and 98.42% for the β-carotene / linoleic acid. The differential pulse voltammetry showed the best results for the butanol fraction and ethyl acetate fraction, the voltagramas showed oxidation and reduction, indicating regenerative capacity. Therefore the data indicated that the leaves of Jacaratia spinosa are sources of phenolic compounds, making potential for use as antifungal and natural antioxidant.